Lighting the way: Compelling open questions in photosynthesis research - Eckardt, Nancy A. (2024)
Photosynthesis—the conversion of energy from sunlight into chemical energy—is essential for life on Earth. Yet there is much we do not understand about photosynthetic energy conversion on a fundamental level: how it evolved and the extent of its diversity, its dynamics, and all the components and connections involved in its regulation. In this commentary, researchers working on fundamental aspects of photosynthesis including the light-dependent reactions, photorespiration, and C4 photosynthetic metabolism pose and discuss what they view as the most compelling open questions in their areas of research.